2012
DOI: 10.1073/pnas.1211775110
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of vesicular zinc efflux by ZIP13 and its implications for spondylocheiro dysplastic Ehlers–Danlos syndrome

Abstract: Significance Intracellular zinc is tightly controlled because zinc is essential but potentially toxic. Many organisms regulate zinc using storage vesicles/organelles, but whether mammals do so is unknown. Here, we show that human ZIP13 releases zinc from vesicular stores. Previous studies found that mutations in the ZIP13 gene, SLC39A13 , cause the spondylocheiro dysplastic form of Ehlers–Danlos syndrome (SCD-EDS) and speculated that ZIP13 exports zinc from the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 58 publications
4
91
0
Order By: Relevance
“…We used MLIV fibroblasts to verify these findings and to examine a possible rescue effect of MK6-83 on lysosomal zinc accumulation. We found that LysoTracker positive compartments of TRPML1 À / À fibroblasts displayed strong vesicular FluoZin-3 fluorescence when pretreated with ZnCl 2 as described previously 45,46 . The zinc accumulation in TRPML1 À / À fibroblasts was not reversible on treatment with MK6-83.…”
Section: Mk6-83 Effects On Trafficking and Lysosomal Zinc Buildupmentioning
confidence: 83%
“…We used MLIV fibroblasts to verify these findings and to examine a possible rescue effect of MK6-83 on lysosomal zinc accumulation. We found that LysoTracker positive compartments of TRPML1 À / À fibroblasts displayed strong vesicular FluoZin-3 fluorescence when pretreated with ZnCl 2 as described previously 45,46 . The zinc accumulation in TRPML1 À / À fibroblasts was not reversible on treatment with MK6-83.…”
Section: Mk6-83 Effects On Trafficking and Lysosomal Zinc Buildupmentioning
confidence: 83%
“…Zn 2+ also may be redistributed from other intracellular sites into M7Vs. These include mitochondria and NADPH oxidase at the plasma membrane, major sites of ROS that liberate Zn 2+ from the mitochondrial matrix and from metallothioneins (16,17,74). Thus, M7Vs may comprise a sink or reservoir buffering cytosolic Zn 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Total Zn 2+ increases by 50% during meiotic maturation of oocytes; about half of this increase is released by vesicular exocytosis within minutes of fertilization (69), and the rest persists through preimplantation (70). Because TRPM7 is required for preimplantation development (71), it will be important to determine if the Zn 2+ -containing vesicles in oocytes and early embryos are M7Vs and how changes in GSH/redox during early development (31,72,73) (16,17,74), comparable to the levels required to fill M7Vs in these studies. Zn 2+ also may be redistributed from other intracellular sites into M7Vs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ZnT5 −/− / ZnT7 −/− cells displayed an exacerbated ER stress response (26). Similarly, KD of Zip7, Zip13, and ZnT3 in cells induced ER stress and higher cell death, indicating the importance of normal zinc homeostasis for ER stress adaptation (27,28,60).…”
Section: Discussionmentioning
confidence: 99%
“…Zip13 induced or potentiated ER stress (26)(27)(28). The role for ZIP14 in ER stress has not been defined.…”
Section: Significancementioning
confidence: 99%